EXAMPLES OF PROVINCIAL GOVERNORS’ JURISDICTIONS IN IUS QUOD AD RES PERTINET IN ROME - Kulauzov, Maša; Milutin, Milan M (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Several topics are covered in the paper. Firstly, a list of sources of law which regulates the issue of the jurisdictions of provincial governors is given form the broader ones to the narrower ones. Jurisdiction of provincial governors used to come into being in the moment of his entrance to the province. In case he leaves it, his jurisdictions would stop and he would become a private individual. The substitution of the personal jurisdiction of provincial governors, which was significantly shaken by the constitution of Caracalla in 212, with the territorial one, appears to be obvious at the end of the Dominate. The governor used to have civil and military jurisdictions. The former included judicial and administrative powers. Judicial jurisdictions were comprised of those in criminal and those in civil matter. Out of scope of the civil matter, only the examples of the jurisdictions of provincial governors in the matter of property law have been covered in this paper, which, according to the tripartition of Gaius, amounts to ius quod ad res pertinet. Provincial governors were authorised to adjudicate on almost all disputes arising from the everyday life during the formation, protection and termination of rights, not only those related to possessio, dominium, and iura in re aliena, but also those in the matter of obligationes and inheritance.